Direct Percutaneous Embolization of a Lymphocutaneous Fistula - Singhal, Soumil; Uthappa, Mangerira Chinnappa (Journal of Clinical Interventional Radiology ISVIR, 2019)
Lymphocutaneous fistula is a rare clinical condition and presents both a diagnostic and a therapeutic challenge. The authors report a case of secondary lymphocutaneous fistula that was undiagnosed and untreated on several occasions but was successfully treated with direct percutaneous embolization.
Keywords: lymphatic; fistula; intervention